2018
DOI: 10.3349/ymj.2018.59.1.154
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Schnitzler's Syndrome without Monoclonal Gammopathy-Associated Chronic Urticaria Treated with Anakinra

Abstract: Chronic urticaria may often be associated with interleukin (IL)-1-mediated autoinflammatory disease, which should be suspected if systemic inflammation signs are present. Here, we report a case of Schnitzler's syndrome without monoclonal gammopathy treated successfully with the IL-1 receptor antagonist anakinra. A 69-year-old man suffered from a pruritic urticarial rash for 12 years. It became aggravated episodically and was accompanied by high fever, arthralgia, leukocytosis, and an elevated C-reactive protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A few cases have shown that monoclonal is not detected in the early stage of this syndrome [ 14 ]. However, monoclonal gammopathy has been reported to be still absent during the entire disease course [ 15 ]. The presence of monoclonal IgM is a mandatory criterion for diagnosing Schnitzler’s syndrome [ 3 ]; however, not all patients had monoclonal IgM at the initiation stage of SchS [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few cases have shown that monoclonal is not detected in the early stage of this syndrome [ 14 ]. However, monoclonal gammopathy has been reported to be still absent during the entire disease course [ 15 ]. The presence of monoclonal IgM is a mandatory criterion for diagnosing Schnitzler’s syndrome [ 3 ]; however, not all patients had monoclonal IgM at the initiation stage of SchS [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schnitzler`s syndrome without IgG or IgM gammopathy described as Schnitzler-like syndrome in the literature is a potentially underdiagnosed entity (13)(14)(15). But the spectrum of Schnitzler-like syndromes may be not restricted to autoinflammatory symptoms with urticarial rash lacking gammopathy (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, this is the first report of SchS without monoclonal gammopathy in Italy. We retrieved only 7 further case reports of patients diagnosed with SchS without monoclonal gammopathy [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%